(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Speech goes in the article about facilities of expressive syntax. Paid attention to appeal, nominative constructions, incomplete. An idea is reasonable, that syntactic expressive facilities are not only marked an artistically-graphic capacity but also have influential internalss.